Tekanan Darah Pasien Hipertensi Dengan Diabetes Melitus Tipe II Di Puskesmas Ngemplak Simongan Kota Semarang - Rukminingsih, Fef; Octasari, Paulina Maya; Dewi, Restu Anita Sukma (Jurnal Farmasi & Sains Indonesia, 2024)
Hypertension is often asymptomatic and if left untreated can cause complications. Hypertension is an increase in systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. The blood pressure target for hypertensive patients with type II diabetes melitus (HT-DMTII) is <130/80 mmHg. The risk of complications increases if blood pressure does not reach the therapeutic target. Ngemplak Simongan Health Center, Semarang City has quite a lot of HT-DMTII patients, who undergo routine check-ups every month. This study aims to determine the achievement of blood pressure targets for HT-DMTII patients at Ngemplak Simongan Health Center, Semarang City. This study is an observational descriptive study using purposive sampling technique. The data used is retrospective data obtained from medical record data of HT-DMTII patients for the period August - October 2023. The inclusion criteria used were patients aged ≥36 years, receiving the same treatment for 2 consecutive months and having blood pressure data for 2 consecutive months. The data taken included medical record number, age, gender, blood pressure data for 2 consecutive months in the period August - October 2023, antihypertensives given and duration of use. From 62 patients, it was known that the majority were female patients 72.58%, aged >60 years as many as 58.06% and those who used antihypertensives for more than 5 years as many as 61.29%. A total of 59 people (95.16%) received single antihypertensive therapy. The most widely used antihypertensive was amlodipin (90.32%). There were 20 patients (32.26%) whose blood pressure reached the target.